Numerical Simulation to Solve Systems of Stochastic Delay Differential Equations - Mahmood, Suliman; Al-Wassouf, Ahmad; Asaad, Amina (Latakia University Journal -Basic Sciences Series, 2020)
In this paper, we propose a numerical technique to simulate the solutions of some stochasticdelaydifferential equations (SDDEs). The proposed technique uses polynomials of fourth degree with five collocation points. A mean-squarestability of numerical technique is studied when was applied to a test model of SDDE with modeling continuous-time discrete wiener process. The study shows that the proposed numerical technique is stable and convergent from order third and half when applied to a test model. The numerical accuracy of the proposed technique was tested by simulating the solution for three nonlinear linear test problems. Numerical results and comparisons with other methods indicated the effectiveness and efficiency of the proposed method.